MANAJEMEN LABA MELALUI AKRUAL DAN AKTIVITAS REAL PADA PENAWARAN PERDANA DAN HUBUNGANNYA DENGAN KINERJA JANGKA PANJANG (STUDI EMPIRIS PADA BEJ) - Rahman, Annisaa; Hutagaol, Yanthi (Jurnal Akuntansi dan Keuangan Indonesia, 2008)
This study investigates 149 Initial Public Offering (IPO) in Jakarta Stock Exchange (JSX) from 1994 up to 2003. In general, this study is aimed to prove whether firms opportunistically manage earnings in the period o f IPO. Specifically this study examines the effect o f earnings management on firm s’ long term performance and provides explanation as well as comparison o f several measures o f earning management and long-term performance. In this study, earnings management is measured by two accrual variables which are discretionary current accruals and discretionary long term accruals and by two var iables o f discretionary real activities through Cash Flow from Operation (CFO) and Cost o f Goods Sold (COGS). In addition, the underperformance phenomenon is measured by market performance (Cumulative Abnormal Return and Buy and Hold Return method) for periods 1 years after IPO, 2 years after IPO and 3 years after IPO ’s date. The hypothesis testing used in this thesis are t test and multiple regression models. The results show (1) earnings management is conducted through accruals but not through real activities manipulation and (2) earnings management affects stock performance 1 year after IPO. Finally this research finds that there is no difference in stock performance for IPO issuers with aggressive and conservative earnings management.